Fabrication of Large-Area Arrays of Vertically Aligned Gold Nanorods - Wei, Wenbo; Wang, Yuru; Ji, Juanjuan; Zuo, Shanshan; Li, Wentao; Bai, Feng; Fan, Hongyou (Nano letters, 2018)
Anisotropic nanoparticles, such as nanorods and nanoprisms, enable packing of complex nanoparticle structures with different symmetry and assembly orientation, which result in unique functions. Despite previous extensive efforts, formation of large areas of oriented or aligned nanoparticle structures still remains a great challenge. Here, we report fabrication of large-area arrays of vertically aligned gold nanorods (GNR) through a controlled evaporation deposition process. We began with a homogeneous suspension of GNR and surfactants prepared in water. During drop casting on silicon substrates, evaporation of water progressively enriched the concentrations of the GNR suspension, which induces the balance between electrostatic interactions and entropically driven depletion attraction in the evaporating solution to produce large-area arrays of self-assembled GNR on the substrates. Electron microscopy characterizations revealed the formation of layers of vertically aligned GNR arrays that consisted of hexagonally close-packed GNR in each layer. Benefiting from the close-packed GNR arrays and their smooth topography, the GNR arrays exhibited a surface-enhanced Raman scattering (SERS) signal for molecular detection at a concentration as low as 10–15 M. Because of the uniformity in large area, the GNR arrays exhibited exceptional detecting reproducibility and operability. This method is scalable and cost-effective and could lead to diverse packing structures and functions by variation of guest nanoparticles in the suspensions.